PHENYTOIN AS A PROPHYLAXIS OF POST-TRAUMATIC SEIZURES IN HEAD TRAUMA PATIENTS AT JAKARTA ISLAMIC HOSPITAL CEMPAKA PUTIH IN 2020-2022 - khairunnisa; Maulana, Tegar; Andra, Dekka; Hamzah, Zainy (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Post-traumatic seizures can occur as a complication of head injury, whether it is immediately after the head injury to months or years after. Phenytoin is an anti-epileptic drug that has been used widely as a prophylaxis for posttraumatic seizures. Method: The study was conducted retrospectively using medical records of head trauma patients in hospitals in 2020-2022 on 54 samples treated up to seven days post-trauma. Samples were obtained which were then analyzed by medical records, looking at the patient's identity, patient diagnosis, seizure symptoms, and history of anti-seizure drugs. Result: Patients given phenytoin prophylaxis [22 (40.7%)] who did not have seizures [18 (33.3%)] were more than patients who had seizures [4 (7.4%)]. Similar results occurred in patients without phenytoin prophylaxis [32 (59.3%)], more patients with no seizures [30 (55.6%)] than those with seizures [2 (3.7%)]. Conclusion: The usage of phenytoin is still not routinely given to post-traumatic head patients at RSIJ Cempaka Putih. The administration is carried out on a case-by-case basis assessment must be carried out in determining the use of phenytoin as a seizure prophylactic so that the benefits outweigh the side effects. For further research, it is recommended to conduct an EEG examination on head trauma patients to determine the diagnosis of post-traumatic seizures/epilepsy and conduct further seizure evaluation. Keywords: Post-trauma seizure; Phenytoin; Prophylaxis; Head Trauma; Jakarta Islamic Cempaka Putih Hospital